Fecal Microbial Changes in Response to Finishing Pigs Directly Fed With Fermented Feed - Tang, Xiaopeng; Zhang, Kai; Xiong, Kangning (Frontiers in Veterinary Science, 2022)
The present study was conducted to investigate the effects of fermented complete feed (FCF) on fecal microbial composition during the whole grower-finisher period. A total 20 pigs (Duroc× Landrace× Yorkshire, 48.74± 1.49 kg) were divided randomly into two groups: CN group (pigs fed with a basal diet), and FCF group (pigs fed with FCF). After a 60-day trial period, 3 pigs with middle-weight from each treatment were selected to get fecal sample for fecal microbiota analyzed. The results showed that the pigs fed with FCF significantly increased OUT numbers, alpha diversity (Simpson index and Shannon index) and beta diversity, which means that FCF increased the fecal microbiota diversity. At the phylum level, Tenericutes, Spirochaetae, Verrucomicrobia and Cyanobacteria abundance were changed in response to pigs fed with FCF; and Christensenellaceae_R-7_group, Treponema_2, Ruminococcaceae_UCG-005, Prevotellaceae_UCG-003, Phascolarctobacterium, Roseburia and Prevotella_9 at the genus level were changed in response to pigs fed with FCF. LEfSe analysis showed that Roseburia and Prevotellaˍ9 genus were the biomarkers of the microbial community in the FCF group. PICRUSt results predicted that altered fecal microbiome caused by FCF might influence infectious diseases: parasitic, transport and catabolism, signal transduction, amino acid metabolism, replication and repair, and xenobiotics biodegradation and metabolism. In conclusion, pig fed with FCF would affect the fecal microbial diversity and composition.